The Role of Employment Satisfaction Mediation on The Effect of Reward on Employee Performance - Nadiyya, Ahsana; Rini, Hesty Prima (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Employees are one of the most important elements in an organization. This study aims to determine the effect of rewards on employee performance through job satisfaction of non-PNS employees at the Kediri District Transportation Office. This research is included in qualitative research with 3 variables which are Reward, Performance, and Job Satisfaction. The sample used was 48 people with a sample determination using saturated non-probability sampling technique. The measurement scale used is the ordinal scale through the Likert scale with the respondent's answer score 1 to 5. The hypothesis testing in this study uses Partial Least Square Structural Equation Modeling (SEM) statistical analysis and descriptive analysis. The results of the study concluded that reward had no significant effect on employee performance. However, through job satisfaction, rewards have a significant influence on performance.